Phenomenology of PTSD and psychotic symptoms - Pepper, Harriet (Array, 2009)
It is well established that PTSD may develop following a traumatic experience such as war combat. In addition it has been noted that such trauma may lead to symptoms of psychosis. Childhood psychological abuse and sexual abuse have also been linked to psychosis. It may be the case that trauma predisposes to the development of psychosis and this can be compared to psychosis of neurodevelopmental origin (schizophrenia)